FORMATION OF THE INTELLECTUAL ELITE OF THE DIPLOMATIC SERVICE - Palagusynets, Rostyslav (International Journal of Innovative Technologies in Social Science, 2020)
The article considers the peculiarities of the formation of the intellectual elite of the diplomatic service. The features of the intellectual elite are highlighted. It is determined that the essential qualities of the intellectual elite include the level of education, innovative way of thinking, professional success and recognition, creativity, motivation, etc. The essence of the concept of "intellectual elite of the diplomatic service" from the point of view of stratification, altimetric, axiological and monistic approaches is revealed. The main tasks of the diplomatic service of Ukraine have been clarified. The author’s interpretation of the intellectual elite of the diplomatic service is formed. It is determined that the formation of the intellectual elite of the diplomatic service is a purposeful process of creating a personality with predetermined features, which involves actions aimed at its development, and includes its conscious self-development to coordinate the activities of government agencies to ensure a common foreign policy. There are four main factors that influenced the formation of the intellectual elite of the diplomatic service: personnel policy of the Foreign Ministry (MFA), including formal and informal requirements for diplomatic personnel, their selection in accordance with applicable law and internal rules and traditions of the MFA; the level of education and general culture of diplomats; acquisition of professional experience and skills in the process of service; involvement in the corporate values of the diplomatic service: understanding of its content, foreign policy objectives and interests of the country, political culture, patriotic and religious values. It is noted that in the formation of the intellectual elite of the diplomatic service a special place is occupied by university education, as a modern university is not only an educational, but also a scientific and cultural center, which trains intellectuals. It is proved that the rationalization of personnel policy as an innovative direction in the development of Ukraine is a necessary and important condition in the work of the diplomatic service and increase the efficiency of their activities. The directions of realization of innovative personnel policy of diplomatic service for the purpose of modernization of foreign policy activity of Ukraine are offered.